2011
DOI: 10.5491/shaw.2011.2.2.148
|View full text |Cite
|
Sign up to set email alerts
|

Workers’ Compensation Insurance and Occupational Injuries

Abstract: ObjectivesAlthough compensation for occupational injuries and diseases is guaranteed in almost all nations, countries vary greatly with respect to how they organize workers' compensation systems. In this paper, we focus on three aspects of workers' compensation insurance in Organization for Economic Cooperation and Development (OECD) countries - types of systems, employers' funding mechanisms, and coverage for injured workers - and their impacts on the actual frequencies of occupational injuries and diseases.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 8 publications
0
7
0
3
Order By: Relevance
“…It is easily predictable that these different means may have significant implications for system performance, including employers' and workers' incentives to improve workplace safety and hence impact the actual occurrence rates of occupational injuries and diseases (SHIN et al, 2011). Thus, policymakers require a high level of realization of policy effects and economic incentives (Wong et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is easily predictable that these different means may have significant implications for system performance, including employers' and workers' incentives to improve workplace safety and hence impact the actual occurrence rates of occupational injuries and diseases (SHIN et al, 2011). Thus, policymakers require a high level of realization of policy effects and economic incentives (Wong et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The International Labor Organization (ILO) estimated that the total cost of work-related injury and illness are 4% of the gross national product of a given country (SHIN et al, 2011). Numerous studies have demonstrated that occupational accidents and work-related diseases are under-compensated (Park and Bhattacharya, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Faktor yang dapat mempengaruhi kondisi internal pegawai diikutsertakan pada penelitian ini seperti faktor yang mempengaruhi kondisi fisik dan psikologis pekerja yaitu adanya jam kerja lembur, perusahaan dengan upah lembur yang cukup tinggi dapat berarti memberikan jam kerja lembur yang banyak kepada pekerjanya, yang dapat mengakibatkan berbagai gangguan fisik maupun psikologis kepada pekerja, seperti kelelahan dan gangguan stress, sehingga pekerja akan lebih rentan mengalami kecelakaan kerja (-Annesigstadlie, 2011). Keikusertaan perusahaan pada program perlindungan pekerja sepert pensiun, tunjangan sosial, asuransi dan sejenisnya akan menimbulkan rasa aman dan nyaman bagi pekerja dalam melaksanakan pekerjaannya, sehingga jumlah kecelakaan kerja pun dapat berkurang (Shin, Oh, & Yi, 2011).…”
Section: Tinjauan Pustakaunclassified
“…Tingkat upah dinyatakan dalam bentuk riil dengan harga dasar tahun 2010 dengan satuan ribu rupiah, sedangkan jumlah tenaga kerja perusahaan ditentukan oleh rasio antara jumlah pekerja pada yang konsisten dengan studi sebelumnya (Holte et al, 2015;Said et al, 2012) dimana jumlah tunjangan kecelakaan kerja lebih besar ditemukan pada perusahaan dengan ukuran yang kecil dikarenakan belum informalnya hubungan kerja pada perusahaan kecil serta masih diacuhkannya peraturan keselamatan kerja yang ada. Sedangkan hasil dari variabel dummy asuransi menunjukkan bahwa perusahaan yang ikut serta dalam program perlindungan pekerja mengeluarkan tunjangan kecelakaan kerja lebih sedikit 44,7% apabila dibandingkan dengan perusahaan yang tidak ikut serta dalam program tersebut, hal tersebu sejalan dengan studi Shin (Shin et al, 2011), dimana adanya keikusertaan perusahaan pada program perlindungan pekerja sepert pensiun, tunjangan sosial, asuransi dan sejenisnya akan menimbulkan rasa aman dan nyaman bagi pekerja dalam melaksanakan pekerjaannya, sehingga jumlah kecelakaan kerja pun dapat berkurang yang berimplikasi kepada pengurangan tunjangan kecelakaan kerja oleh perusahaan.…”
Section: Hasil Dan Pembahasanunclassified
“…Glosas de innovación aplicadas a la pyme. ISSN: 2254-4143 256 cost of work-related illness and injury are 4% of the gross national product of a given country (Shin, Oh, & Yi, 2011)countries vary greatly with respect to how they organize workers' compensation systems. In this paper, we focus on three aspects of workers' compensation insurance in Organization for Economic Cooperation and Development (OECD .…”
Section: Introductionmentioning
confidence: 99%